Grid codes for renewable powered systems (International Renewable Energy Agency, 2022)
This report contains the latest developments and good practices to develop grid connection codes for power systems with high shares of variable renewable energy - solar photovoltaic and wind. The analysis is an update of the 2016 IRENA report Scaling up variable renewable power: The role of grid codes. There is an urgent need to adopt clean energy solutions to cope with growing demand for energy and replace existing polluting generators. The inclusion of variable renewable energy introduces challenges to system operation. As renewable energy is variable, uncertain, location constrained and inverter-based, replacing conventional synchronous generation technologies. Furthermore, the power system is becoming more decentralised, digitalised and end-use sectors more electrified. These trends are driving the growth of the power system in a new and different direction. All of this comes at a cost to the system operation, which has to ensure that the system is stable at all times.
Keywords: Electric power distribution.; Renewable energy sources.; elektronické knihy; electronic books